Mechanisms to Prevent Corruption in the Constitutional Amendment 2020 - Khalfallah, Chemseddine; Saadi, heidra (Journal of Legal Studies and Researches, 2022)
Given the importance of interests that have become threatened by corruption and crimes. This has become the focus of legal texts. The Algerian constitution has many mechanisms that would prevent these crimes, which we aim to highlight in this study. We concluded that Algeria has a constitution prevents corruption crimes, but this strategy has been deficient in many of its rules.